Simulation of a Crash Test of a Single-Track Vehicle in a Frontal Collision- Part2 - Marek STEMBALSKI; Rafal FENC (Communications of International Proceedings, 2021)
The article continues with the results of a crash test simulation of an electric scooter frame during a frontal collision with a non-deformable wall. The presented article is the second part of the research and describes the simulation resulted in a frontal crash test at 85 km/h. Detailed results of the frontal crash test simulation at 45 km/h are described in the first part of the research. In the final stage of the article, the kinetic energy to total energy relationship for the frontal crash test was determined and the results were compared for the 45 km/h and 85 km/h cases. The simulation was made by using CAD systems. The geometric model was made using SolidWorks software while the computational model was made using Abaqus CAE software. Strength calculations were performed based on the finite element method. The computational model was performed using shell elements.
Keywords: Crash Test; Single-Track Vehicle; CAD System; Numerical Simulation; Mechanical Engineering